KESELAMATAN KERJA PADA KARYAWAN PT. E STRONG NUSANTARA MANDIRI - Pamungkas, Yogo; setiawati, Anda; Achdianto; Yoga Pamungkas (Universitas Trisakti, 2024)
Workforce protection is important because work safety will also greatly affect work productivity and also lead to company profits. Comfortable work activities from workers will also make the quality of work relationships higher. Worker satisfaction is related to variables such as role conflict, turnover intentions and results and so much work has been done in organizational management. PT. E Strong Nusantara Mandiri is a company engaged in the chemical sector with workers who carry out their activities directly related to chemicals. Therefore, knowledge about Occupational Health and Safety is very important. The problem raised is how to provide knowledge to workers at PT. E Strong Nusantara Mandiri about the importance of occupational safety and health and how to provide awareness to implement occupational safety and health for workers at PT. E Strong Nusantara Mandiri. The method of implementing this activity begins with identifying the problem by conducting an interview with the director of PT. E strong Nasusantara Mandiri. The data from the interview results are analyzed as a basis for formulating the form and technical implementation of the activity. The formulation of the activity is then made into a proposal to obtain adequate support from the Community Service Institution and PT. E Strong Nusantara Mandiri. In the implementation of the extension activity, the lecture, discussion and simulation methods are used. Finally, an incidental consultation is held. The results of this activity are that workers at PT. E Strong Nusanatara Mandiri do not yet understand about Occupational Health and Safety so that this activity provides significant input for workers